Penerapan Prinsip E-Government dalam Administrasi Pemerintahan Digital: Tantangan Regulasi dan Perlindungan Hukum Warga Negara - Faddillah Islam, Gita; Sulastri, Dewi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The digital transformation of government through the implementation of e-government has become an inevitable necessity in the era of the industrial revolution 4.0. This study aims to analyze the application of e-government principles in digital public administration in Indonesia, identify regulatory challenges, and examine the forms of legal protection for citizens. This research employs a normative juridical method with statutory and conceptual approaches, supported by case studies of digital government platforms. The findings indicate that the implementation of e-government in Indonesia has been carried out through the Electronic-Based Government System (SPBE), yet it remains partial and not fully integrated. Major challenges include regulatory disharmony, legal gaps, data protection issues, limited infrastructure, and sectoral ego among government institutions. Furthermore, legal protection for citizens has not been fully effective, particularly in ensuring privacy rights and administrative accountability. Therefore, comprehensive regulatory reform, strengthened personal data protection, and institutional capacity building are necessary to achieve a fair and citizen-oriented digital governance system.